2017
DOI: 10.1021/acs.jpcb.6b11425
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Nanocellulose Using Small-Angle Neutron, X-ray, and Dynamic Light Scattering Techniques

Abstract: Nanocellulose extracted from wood pulps using TEMPO (2,2,6,6-tetramethylpiperidine-1-oxyl radical)-mediated oxidation and sulfuric acid hydrolysis methods was characterized by small-angle neutron scattering (SANS), small-angle X-ray scattering (SAXS), and dynamic light scattering (DLS) techniques. The dimensions of this nanocellulose (TEMPO-oxidized cellulose nanofiber (TOCN) and sulfuric acid hydrolyzed cellulose nanocrystal (SACN)) revealed by the different scattering methods were compared with those charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
109
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(133 citation statements)
references
References 50 publications
24
109
0
Order By: Relevance
“…A shoulder feature was found at around q = 1 nm −1 for cellulose both before and after treatment with cellulase. This could be explained by the presence of highly dispersed cellulose microfibrils with sharp interfaces with the solvent, as was found in previous studies [16,17]. The higher q-region of this shoulder feature (1.5-2.5 nm −1 ) was successfully fitted using the power law in the form I (q) ∝ q −D , where D = 4 for both samples, as shown in Fig.…”
Section: Saxs Analysissupporting
confidence: 78%
“…A shoulder feature was found at around q = 1 nm −1 for cellulose both before and after treatment with cellulase. This could be explained by the presence of highly dispersed cellulose microfibrils with sharp interfaces with the solvent, as was found in previous studies [16,17]. The higher q-region of this shoulder feature (1.5-2.5 nm −1 ) was successfully fitted using the power law in the form I (q) ∝ q −D , where D = 4 for both samples, as shown in Fig.…”
Section: Saxs Analysissupporting
confidence: 78%
“…Although the cellulose molecular backbone is common to all; surface morphology, size, chemical and physical properties can vary greatly depending upon the material source and extraction methods used (Mao et al, 2017). The objective of this study was to examine the physicochemical properties of NC fibrils, CNCs and a novel blend of these materials produced via the AVAP® technology.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have demonstrated the usefulness of scattering techniques to determine the dimensions of dispersed NC. Statistically averaged cross section dimensions of CNC and CNF can be determined by means of small-angle neutron scattering and small-angle X-ray scattering [133] by modeling them as rigid parallelepipeds with very high aspect ratio as the length of nanofibrils is much larger than their section. The use of dynamic light scattering (DLS) for dimensional characterization of NC presents several challenges: First, it requires dust-free sample preparation because microparticles of dust movement is much slower than that for nanocellulosic particles and they can saturate the detector resulting in a false measurement result.…”
Section: Dimensions and Structurementioning
confidence: 99%
“…The use of dynamic light scattering (DLS) for dimensional characterization of NC presents several challenges: First, it requires dust-free sample preparation because microparticles of dust movement is much slower than that for nanocellulosic particles and they can saturate the detector resulting in a false measurement result. Second, the length of NC particles usually reaches the submicron or even micron scale which makes both DLS measurement and data interpretation challenging [133]. Finally, DLS gives the hydrodynamic dimensions assuming that particles are spheres and the particle size is determined from that considering that the particle concentration is low enough to assure that diffusion takes place only by means of Brownian movement and the aggregation of particles is impaired; particle flexibility and surface charge can interfere the measurement too [134].…”
Section: Dimensions and Structurementioning
confidence: 99%